POTENTIAL ANALYSIS OF THE AGRICULTURAL, FORESTRY, AND FISHERIES SECTORS IN BANDUNG REGENCY BEFORE AND DURING THE COVID-19 PANDEMIC - Putri Siti Awaliyah; Agustono Agustono; Mei Tri Sundari (Universitas Galuh, 2023)
Bandung Regency is an agricultural area that supports the business development of various commodities. However, the growth rate and contribution of the agricultural, forestry, and fishery sectors in Bandung Regency is relatively small. The existence of the Covid-19 pandemic has caused a decrease in economic activity which has an impact on the economic structure in GRDP, this causes the need for an analysis to determine the potential of the agricultural, forestry and fisheries sectors in Bandung Regency seen from its growth. This research uses primary data from interviews and secondary data from the GRDP of Bandung Regency and West Java Province in 2016-2019 for the period before the pandemic and 2020-2021 for the period during the Covid-19 pandemic. There are two analytical methods used, namely Shift Share Analysis (SSA) and Growth Ratio Model (GRM). The results of the shift share analysis show that the agricultural, forestry, and fisheries sectors in Bandung Regency have a positive total economic change value, meaning that the sector has the potential to be developed both before the pandemic and during the Covid-19 pandemic, while the results of the growth ratio model analysis show that the agricultural, forestry, and fisheries sectors in Bandung Regency had regional potential before the pandemic, but became not potential during the Covid-19 pandemic.